Do pre‐operative knee laxity values influence post‐operative ones after anterior cruciate ligament reconstruction?. Issue 4 (26th February 2013) - Signorelli, C.; Bonanzinga, T.; Lopomo, N.; Marcheggiani Muccioli, G. M.; Bignozzi, S.; Filardo, G.; Zaffagnini, S.; Marcacci, M.
Abstract : The objective of this study was to verify whether pre‐reconstruction laxity condition effects post‐reconstruction outcome. A total of 100 patients who underwent navigated Anterior Cruciate Ligament (ACL) reconstruction were included in the study and knee laxity analysed retrospectively. The knee was assessed in six different laxity tests before and after ACL reconstruction, namely antero‐posterior (AP) and internal‐external (IE) at 30° and 90°, and varus‐valgus (VV) rotations at 0° and 30° of flexion. For each test, the least square (LS) fitting line based on pre‐operative‐to‐post‐operative laxity value was calculated. To what degree the post‐operative laxity value is explainable by the corresponding pre‐operative condition was evaluated by the LS line slope. Post‐operatively, for each single patient, the grade of laxity decreased at any evaluated test. The strongest influence of pre‐operative‐to‐post‐operative laxity values was found during IE30 and IE90 tests. While AP30 and VV0 tests seem to be those in which the post‐reconstruction laxity was barely affected by the pre‐surgery condition. The analysis of the global laxity reduction confirms the previous results. Following this hypothesis, our study remarks on the importance of combined lesions to secondary restraints and the importance of fully understanding the residual laxity to optimize the surgical technique.